Efficacy of a modified saline solutions for the survival of Tetraphyllidean plerocercoids from the scallop (Argopecten purpuratus) - Castro, Teresa (2021)
The aim of this study was to obtain a modified saline solution that allows a longer survival for the morphological study of Tetraphyllideans plerocercoids from the scallop Argopecten purpuratus. Two temperatures were evaluated: T-1, room temperature and T-2, constant temperature of 0.5 °C and five solutions: A = FSS (physiological saline solution – FSS – 0.85%), B = ¼ SW (sea water) + ¾ FSF, C = ½ SW + ½ FSS, D = ¾ SW + ¼ FSS, E = SW. One hundred live larvae freshly extracted from A. purpuratus gonads (10 per experimental group) were used for 13 days. The longest survival was observed in T-1 solutions B and C, where four plerocercoids remained alive until day 10 and three until day 12, respectively. With the exception of solution A, the larvae maintained their normal activity and shape in the rest of the solutions until day 6. This work shows that the usual saline solutions (0.75 to 0.9%) may not be optimal for keeping marine plerocercoids alive and that a salinity approaching seawater is more appropriate.